Konstruksi Citra Diri melalui Media Sosial Instagram - Muthia Febrianti Satari Atmadiwangsa; Neni Yulianita (UNISBA Press, 2022)
Abstract. This research is motivated by the phenomenon that occurs on Instagram social media as an event to show. In general, the use of social media Instagram to form a self-image that can be liked by many people in the community. Self-image is a self-image that becomes an assessment so that someone who intentionally uses social media as a goal so that it can be known according to the individual's goals, the self-image shown by Instagram celebrities will affect people who see it so that they can create new views for everyone else who sees it. see that researchers are interested in researching the Construct of Self-Image through Instagram Social Media on the Instagram account @dindamaulinaaa using qualitative research methods with case study approach analysis, in constructing self-image through Instagram social media, Dinda has utilized its use well and produced positive impressions from her followers . In the process of constructing Dinda's self-image, there were no obstacles, Dinda formed a positive self-image so that Dinda's followers could think positively of Dinda as well. The reason for maintaining self-image on Instagram comes from Dinda's self-awareness, because Dinda as an Instagram celebrity who has a large number of followers, therefore Dinda tries to become a